Justification of the optimal ratio of components in macaroni products enriched with composite mixture - Aptrakhimov, Denis; Mardar, Maryna; Evtushenko, Anatolie; Smolnikova, Farida; Prokhasko, Lubov; Rebezov, Maksim; Khayrullin, Mars (International Journal of Engineering and Technology, 2018)
This article presents the results of mathematical calculations of nutritive value of macaroni product enriched with composite mixture. While creating the paste there was developed a composite mixture containing high-grade wheat flour, buckwheat and flax flour, and a characteristic of its biological value was obtained.Â Â Â Â